Evaluating exotic predator control programs using non-invasive genetic tagging - Piggott, Maxine P; Wilson, Rebecca; Banks, Sam C; Marks, Clive A; Gigliotti, Frank; Taylor, Andrea C (Wildlife research (East Melbourne), 2008)
Carnivorous predators are difficult to detect using conventional survey methods, especially at low levels of abundance. The introduced red fox (Vulpes vulpes) in Australia is monitored to determine the effectiveness of control programs, but assessing population parameters such as abundance and recruitment is difficult. We carried out a feasibility study to determine the effectiveness of using faecal DNA analysis methods to identify individual foxes and to assess abundance before and after lethal control. Fox faeces were collected in two sampling periods over four separate transects, and genotyped at five microsatellite loci. Two transects were subject to lethal control between collection periods. DNA was extracted from 170 fox faeces and, in total, 54 unique genotypes were identified. Fifteen biopsy genotypes from 30 foxes killed during lethal control were detected among the faecal genotypes. Overall, a similar number of genotypes were detected in both sampling periods. The number of individuals sampled in both periods was low (n=6) and new individuals (n=24) were detected in the second collection period. We were also able to detect animals that avoided lethal control, and movement of individuals between transects. The ability to identify individual foxes using these DNA techniques highlighted the shortcomings of the sample design, in particular the spatial scale and distances between transects. This study shows that non-invasive DNA sampling can provide valuable insight into pre and post fox abundance in relation to lethal control, individual behaviour and movement, as well as sample design. The information gained from this study will contribute to the design of future studies and, ultimately, control strategies.